S111 Altered neutrophil phenotypes in pulmonary arterial hypertension. (15th November 2017) - Dirir, O; Lodge, KM; Creaser-Myers, A; Walker, S; Kiely, DG; Condliffe, AM; Lawrie, A; Thompson, AAR
Abstract : Introduction: Evidence has implicated neutrophil elastase (NE), a proteolytic enzyme, as a key driver of the pulmonary vascular remodelling that underlies pulmonary arterial hypertension (PAH). Moreover, studies using animal models and explanted human lung tissue have demonstrated that inhibition of NE attenuates pulmonary hypertension. However, there has been little investigation into neutrophil function in PAH patients even though their azurophilic granules are the main physiological reservoir of NE. We investigated neutrophil phenotypes in patients with PAH versus healthy controls, with a focus on neutrophil degranulation. Methods: Neutrophils were isolated from venous blood of PAH patients and healthy controls (HC) and treated with LPS; viability was assessed at 20 hours by morphology. Cell surface receptor expression was determined by flow cytometry. To evaluate degranulation, neutrophils were treated with priming agents, platelet activating factor (PAF, 1 µM) or tumour necrosis factor-α (TNF, 20 ng/ml), and subsequently stimulated with N-formylmethionyl-leucyl-phenylalanine (fMLP; 100 nM). NE release was measured by ELISA and released NE activity and myeloperoxidase (MPO) activity were determined by fluorogenic (Enzchek) and colorimetric (o-dianisidine oxidation) assays respectively. Results: Neutrophil apoptosis 20 hours following stimulation with LPS was significantly lower in PAH (25.4%+/-2.2, n=12) versus HC samples (44.9%+/-4.7, n=9), p<0.001. There were no differences in TLR2 or TLR4 expression between PAH and HC neutrophils. PAH neutrophils released greater amounts of NE following stimulation (e.g., TNF-α priming: PAH 675.2 ng/ml+/-77 vs. HC 277 ng/ml +/−18.4, p<0.0001) but there was no increase in NE activity in the same supernatants, nor any difference in released MPO activity compared to healthy controls. Conclusions: Our Results indicate that neutrophil phenotype is altered in PAH, with a prolonged lifespan in response to a pro-inflammatory stimulus and increased release of NE. However, we did not detect a corresponding increase in NE activity, suggesting a concomitant increase in NE inhibitor release from PAH neutrophils. The potential role of this altered neutrophil phenotype in vascular remodelling requires further investigation.